Online language games for pre-degree students / Anealka Aziz Hussin , Tuan Sarifah Aini Syed Ahmad and Eliyas S. Mohandas - Aziz Hussin, Anealka; Syed Ahmad, Tuan Sarifah Aini; Mohandas, Eliyas Sulaiman (UiTM Press, 2017)
Students like to play online games and some of them are found to be addicted to certain online games. However, when ask about playing educational games especially language games, the responses are not very encouraging. For many, language games are for juvenile, and not suitable for college level students like them. This study intends to show that language games are relevant even to college level students. Several online games were developed based on the learning outcomes of an undergraduate English language course. The games were designed at different difficulty levels based on the Bloom's Taxonomy. 34 pre-degree students (7 males and 27 females) from Universiti Teknologi MARA (UiTM) Negeri Sembilan participated in the study. They were asked to try the games and give feedback on what they think of the games. Results of the survey showed that the students were motivated to play the games, and they believed that they could improve their language skills by playing the games.